147k views
0 votes
- 7x + 5(2x - 1) = -20​

User Alok Singh
by
5.5k points

2 Answers

3 votes

Answer:

x = -5

Explanation:

-7x + 5(2x - 1) = -20 (Given)

-7x + 10x - 5 = -20 (Simplify)

3x - 5 = -20 (Simplify)

3x - 5 + 5 = -20 + 5 (Addition Property of Equality)

3x = -15 (Simplify)


(3x)/(3) = (-15)/(3) (Division Property of Equality)

x = -5 (Simplify)

User Metalheart
by
6.0k points
7 votes

Answer:

x= -5

Explanation:

-7x + 5(2x - 1) = -20

-7x + 10x - 5 = -20

3x -5 = -20

3x = -15

x = -5

User LeeMobile
by
6.8k points